2012
DOI: 10.1016/j.comcom.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Are friends overrated? A study for the social news aggregator Digg.com

Abstract: The key feature of online social networks (OSN) is the ability of users to become ac>ve, make friends and interact via comments, videos or messages with those around them. This social interac>on is typically perceived as cri>cal to the proper func>oning of these plaSorms; therefore, a significant share of OSN research in the recent past has inves>gated the characteris>cs and importance of these social links, studying the networks' friendship rela>ons through their topological proper>es, the structure of the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
(41 reference statements)
0
22
0
1
Order By: Relevance
“…These studies have focused, for example, on characterizing how content is propagated within the network and on identifying the most popular and the most influential users [3]. Some studies have shown that users maintain large networks of contacts, but these networks have little effect on the content they consume [8]. This challenges the belief that relationship Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have focused, for example, on characterizing how content is propagated within the network and on identifying the most popular and the most influential users [3]. Some studies have shown that users maintain large networks of contacts, but these networks have little effect on the content they consume [8]. This challenges the belief that relationship Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated how content shared in a UGC is valued by users and disseminated through their contacts in the social network [3,4,8,13]. These studies have focused, for example, on characterizing how content is propagated within the network and on identifying the most popular and the most influential users [3].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of metric convergence will be conducted on the network topology of friend and follower relations within the social media aggregator Digg.com, for which a complete graph topology was collected and presented in [3]. The complete graph was obtained by the simultaneous monitoring of the Digg.com system from four different dimensions, (1) a retrieval of all content items (called "stories") submitted and listed in the platform, (2) a monitoring of all persons who commented or voted on a particular story, (3) a collection of activities performed by an individual person and (4) the tracking of all persons linked to a user by a follower or friend relation.…”
Section: Metric Convergencementioning
confidence: 99%
“…Second, the network is still manageable enough to repeatedly compute and analyze the stability of network metrics and the dynamics of different crawling methodologies. Third, using the four-dimensional data acquisition presented in [3], a complete trace of the entire social network topology was obtained, thus making an evaluation of crawling methodologies and convergence of common topological metrics possible in the first place.…”
Section: Introductionmentioning
confidence: 99%
“…Eles também encontraram evidências de uma série de mecanismos pelos quais a influência social é transmitida. Doerr et al [2012] apresentaram resultados de um estudo de vários anos da rede Digg.com, observando a importância dos amigos e da rede de amigos na propagação de informações. Seus resultados indicam a presença de fatores anteriormente desconsiderados, como o alinhamento temporal entre as atividades do usuário e a existência de outras relações lógicas além da topologia do grafo social, que são capazes de conduzir e orientar a dinâmica da rede.…”
Section: Interações Sociais Baseadas Em Vídeounclassified